Elastic interactions between nano-scale defects in irradiated materials. (15th February 2017) - Dudarev, S.L.; Sutton, A.P.
Abstract: Closed form expressions are derived for the energy of elastic interaction between dislocation loops, and between dislocation loops and vacancy clusters, to enable simulations of elastically biased microstructural evolution of irradiated materials. The derivations assume the defects are separated by distances greater than their size. The resulting expressions are well suited for real-space simulations of microstructural evolution involving thousands of elastically interacting defects in 3D. They play a similar role to interatomic potentials in molecular dynamics simulations. Graphical abstract: Image 1